ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF PEREKONOMIAN KOTA PADANG SEBAGAI PUSAT KEGIATAN NASIONAL SUMATERA BARAT (JURNAL ECONOMICA : Research of Economic And Economic Education, 2017)
AbstractThis study focuses on  the comparative and competitive  economic advantages of Padang City in order to determine the economic development priorities in the future. The analytical approach of this research  is a regional economic analysis approach with Location Quoatient (LQ) and Shift and Share analysis (SSA) method. The secondary data used in this study is collected from the Central Bureau of Statistics and Bank of  Indonesia. The results shows that there are 15 sectors which strong economic based  in Padang economics. This is indicated by the LQ value which greater than 1 during the period of 2011 until 2015. The manufacturing sector includes the major trade and retail which has been the main focus of the economic development of Padang City, has decreased its comparative and competitive advantages in West Sumatra region. Padang City as National Activity Center should be a major trading and retail center in West Sumatera. On the demand side, the economy of Padang City is experiencing a fundamental problem, because of  its exports not yet have a strong and solid based. Gross fixed capital formation which shows a good investment progress has less comparative advantage, but it has a regional competitive advantage. Therefore, the economic development of Padang City is more focused on enhancement of trading sector. Keywords : Comparative, Competitive Advantages and National Activities Center